Multivariate polygenic models in personalized psychiatry - М. V. Alfimova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Personalizing patient care through the use of individual genome-wide information is one of the key challenges for psychiatry in the post-genomic era. Prognostic multivariate models incorporating polygenic risk scores (PGRS) seem to be a promising tool. The article discusses the potential of fully polygenic models, in which all predictors are represented as PGRS of the corresponding phenotypes, and models, in which the individual genetic information embedded in the PGRS is supplemented with epigenetic data.